Ocean Modelling in Support of Operational Ocean and Coastal Services - Sotillo, Marcos G. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Operational oceanography is maturing rapidly. Its capabilities are being noticeably enhanced in response to a growing demand for regularly updated ocean information. Today, several core forecasting and monitoring services, such as the Copernicus Marine ones focused on global and regional scales, are well-stablished. The sustained availability of oceanography products has favored the proliferation of specific downstream services devoted to coastal monitoring and forecasting. Ocean models are a key component of these operational oceanographic systems (especially in a context marked by the extensive application of dynamical downscaling approaches), and progress in ocean modeling is certainly a driver for the evolution of these services. The goal of this Special Issue is to publish research papers on ocean modeling that benefit model applications that support existing operational oceanographic services. This Special Issue is addressed to an audience with interests in physical oceanography and especially on its operational applications. There is a focus on the numerical modeling needed for a better forecasts in marine environments and using seamless modeling approaches to simulate global to coastal processes.